Association between Systemic Inflammatory Immunity Index and Intracoronary Thrombus Burden in Acute Myocardial Infarction with ST Segment Elevation (IMA EST) Patients Undergoing Primary Percutaneous Coronary Intervention at Haji Adam Malik Hospital - Dhilion, Har Rawishwar Singh; Nasution, Ali Nafiah; Sitepu, Andika (Journal of Society Medicine, 2024)
Introduction: Acute coronary syndrome (ACS) account for 30% of deaths worldwide. High peri-procedural intracoronary thrombus burden is a strong predictor of poor outcome. Inflammation plays an important role in the pathogenesis of intracoronary thrombus formation. The systemic inflammatory immunity index represents the immune responses to inflammation, which consist of neutrophilia, thrombosis and decreased lymphocytes. The previous study showed that systemic inflammatory immunity index predicted high intracoronary thrombus burden in STEMI patients. This study aimed to evaluate systemic inflammatory immunity index in predicting the incidence of high intracoronary thrombus burden in STEMI patients. Method: This research is a retrospective analytical observational study on 95 patients diagnosed with ACS in the period 1 January 2022-31 March 2023 at H. Adam Malik General Hospital, Medan. All patients involved had undergone primary percutaneous coronary intervention. Patient characteristics, risk factors, laboratory results and coronary angiography were recorded from the patient's medical record. Results: There was a significant relationship between the systemic inflammatory immunity index value and the incidence of high intracoronary thrombus burden in STEMI patients (P < 0.001). The systemic inflammatory immunity index cut off point value > 1108 has a sensitivity of 89.4% and a specificity of 89.7% which has a better accuracy in predicting high intracoronary thrombus burden in STEMI patients. Conclusion: Systemic inflammatory immunity index has a good accuracy to predict high intracoronary thrombus burden in STEMI patients.